The effect of chain extender structure on the enzymatic degradation of carbohydrate based polyurethane elastomers - Wojturska, Joanna (Polimery, 2020)
Polyurethane elastomers (PUR) based on 2,2,4(2,4,4)-trimethyl-hexamethylenediisocyanate (TMDI) and polyestrodiol (Desmophen D1200) were prepared using various carbohydrates or their derivatives: monosaccharide (glucose), disaccharide (sucrose), sugar alcohol (mannitol and sorbitol). The effect of stoichiometry of ingredients and type of carbohydrates is discussed in relation to their susceptibility to enzymatic degradation catalysed by lipase from Candida antarctica (Novozym 735). The study supports the suitability of carbohydrates or sugar alcohols as important components of PUR for biomedical applications.